Analysis of the failure of primary support of a deep-buried railway tunnel in silty clay. (August 2016) - Kong, Chao; Gao, Xinqiang; Cao, Li; Liu, Kai
Abstract: This paper analyses the mechanism for the failure of primary support of a deep-buried tunnel whose side wall collapses during construction. The main focus is on discussion and comparison of the soil engineering aspects of the incident, and on the lessons that may be learnt from the case. Empirical and numerical analysis have been carried out for the collapse. The mechanisms of failure of tunnel are analyzed during tunnel excavation and the parameters of support are revised according to the results of analysis. Results have shown that the collapse of tunnel is mainly attributed to abundant joint fissures on surrounding soil. The changed support makes tunnel drive through the section of collapse successfully, and similar dangerous situation does not take place in the following construction. Highlights: The paper elaborates the process of the Yangjialing tunnel's collapse. Joint fissure on surrounding soil is the one of reasons for tunnel's collapse. Inhomogeneous joint fissures make primary lining understand asymmetrical load. Through the analysis, relevant experience and lessons are summarized.